Zadrzanie amínokyseliny v bachorovom epiteli oviec - Faixová, Z; Várady, J (Veterinarni medicina, 1997)
By the modification of the methods which are used for determination of amino acid uptake in the mammary gland and in the small intestine the uptake of 14C-lysine was measured in two parts of the sheep rumen epithelium in vitro. Three various lysine concentrations were used (0.95; 4.95 and 9.95 mM/l). Duration of the incubation was 15, 30 or 60 minutes. Comparison of the lysine distribution ratios as depending upon the duration of incubation period in the dorsal rumen sac at 9.95 mM/l concentration revealed significant differences between at the 15 min and 60 min incubation (0.952 +/- 0.089 vs 1.931 +/- 0.108; P < 0.05, respectively) and between 30 min and 60 min incubation (1.165 +/- 0.138 vs 1.931 +/- 0.108, P < 0.05, respectively)-Fig. 1. Comparison of the lysine distribution ratios as depending upon the duration of incubation period in the ventral rumen sac at 4.95 mM/l concentration revealed significant differences between the incubations of 15 and 30 min (1.182 +/- 0.131 vs 1.742 +/- 0.113; P < 0.05, respectively) and between the incubations of 15 and 60 min (1.182 +/- 0.131 vs 2.10 +/- 0.204; P < 0.05, respectively)-Fig. 2. Comparison of the lysine distribution ratios in both the dorsal and ventral sac as depending upon the duration of incubation period after 15 min incubation revealed a significant difference at the 4.95 mM/l concentration 1.619 +/- 0.078 vs 1.182 +/- 0.131; P < 0.05, respectively)-Fig. 3. Our results showed that the lysine uptake in the dorsal and ventral sheep rumen epithelium is dependent on the incubation duration only under certain concentrations of lysine. Differences in absorption of lysine between dorsal and ventral rumen epithelium are not mostly significant.
Keywords: ovce; Epithelium; bachor; ženské pohlaví; epitel; zvířata; lysin; Rumen; Female; Sheep; Animals; Lysine